Leiomyoma of the Cheek - Ricardo Roberto de Souza Fonseca; Mário Augusto Ramos Junior; Douglas Baruchi; Tabata Resque Beckmann Carvalho; Andresa Borges Soares; Silvio Augusto Fernandes de Menezes; João de Jesus Viana Pinheiro; Jorge Nazareno Ferreira Fadul (Case Reports in Pathology)
Leiomyomas are rare benign tumors that grow in the tunica media of smooth muscle cells. Leiomyomas occur most frequently in the uterus or gastrointestinal tract and only very rarely in the area of the cheek. This study reports on a rare case of a leiomyoma in the cheek of a 43-year-old woman, who presented with a well-circumscribed, asymptomatic, mobile swelling in the right cheek. This swelling was slightly purplish in color and measured approximately 4 cm×3 cm. Surgical excision was the treatment of choice, and the diagnosis was based on histopathological and immunohistochemical stains, which were positive for actin and desmin and negative for AE1/AE3, CD34, and S100. The patient’s follow-up, two years later, showed no recurrence, and she has been asymptomatic since the surgery.